Eksistensi Kepala Daerah Perempuan Terhadap Performa Ekonomi Daerah Di Indonesia - Muhammad Bagus Sistriatmaja; Bhimo Rizky Samudro; Dwi Prasetyani (Prosiding, 2022)
This study aims to look at the existence of women as regional heads and their performance in the economic dimension. The descriptive method is employed to investigate the pattern using district/city regional data in Indonesia from 2015-2018. The data consist of economic dimensions using Gross Regional Domestic Income (GRDP) and Unemployment. The results of the study indicate that the existence of women in leading executive institutions is on average able to improve economic performance based on the GRDP indicator; but on the other hand on average it has not been able to solve the unemployment problem.